2019
DOI: 10.1136/ijgc-2019-000932
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Swede score colposcopy scoring system and histopathological results in patients with high-risk HPV infection other than HPV16 and 18

Abstract: ObjectiveTriage with HPV genotyping has some caveats and debates for HPV positive cases other than 16 and 18. The Swede score colposcopic scoring system has not previously been evaluated in this group of patients.ObjectiveTo use the Swede score colposcopic scoring system to compare scores and final histopathological results in women who have undergone colposcopy owing to infection with high risk-HPVs other than HPV16 and 18 and to establish new cut-off values to predict pre-malignant lesions in this group of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
7
2
Order By: Relevance
“…The evaluating study was performed at a single centre with only seven colposcopists. A recent Turkish clinical study also found Swedescore performance to be superior to that in the current study 5 …”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The evaluating study was performed at a single centre with only seven colposcopists. A recent Turkish clinical study also found Swedescore performance to be superior to that in the current study 5 …”
Section: Discussioncontrasting
confidence: 68%
“…A recent Turkish clinical study also found Swedescore performance to be superior to that in the current study. 5 We found no cutoff level, based on the Swedescore alone, at which the clinician could safely refrain from taking a punch biopsy. The sensitivity was 89% at Swedescore ≥4, entailing a more than 10% risk of CIN2+.…”
Section: Interpretationsmentioning
confidence: 65%
See 1 more Smart Citation
“…Alan et al detected 34.2% HR‐HPV in their hospital‐based study 21 . The studies attributed their high HPV prevalence to a high rate of abnormal cytology, hospital‐based patients, higher educational status of their patient population, and use of more sensitive HPV detection methods 22–26 . The results of Turkey's HPV screening program, which contains four million women, reported that 4.39% of screened women in the community were HPV DNA positive 16 .…”
Section: Discussionmentioning
confidence: 99%
“…21 The studies attributed their high HPV prevalence to a high rate of abnormal cytology, hospital-based patients, higher educational status of their patient population, and use of more sensitive HPV detection methods. [22][23][24][25][26] The results of Turkey's HPV screening program, which contains four million women, reported that 4.39% of screened women in the community were HPV DNA positive. 16 This rate is lower than other studies because this result represents community and not only HR-HPV types, but also other HPV types.…”
Section: Discussionmentioning
confidence: 99%